Achieving 31% efficiency in organic photovoltaic cells under indoor light using a low energetic disorder polymer donor. Issue 2 (16th December 2022) - Bi, Pengqing; An, Cunbin; Zhang, Tao; Chen, Zhihao; Xu, Ye; Cui, Yong; Wang, Jianqiu; Li, Jiayao; Wang, Yafei; Ren, Junzhen; Hao, Xiaotao; Zhang, Shaoqing; et al.
Abstract : A series of wide bandgap terpolymers are designed and synthesized, which exhibit low energetic disorders. Based on the terpolymers, outstanding PCEs of over 31% (1000 lux) for an indoor OPV cell and over 18.2% (one-sun) for an OPV cell are achieved. Abstract : Polymer donors with wide bandgaps and low energetic disorders are critical for fabricating high-performance indoor organic photovoltaic cells (IOPVs). Herein, a series of polymers (PB3, PB4 and PB5 ) based on thiadiazole (TDZ), 4, 8-bis(5-(2-ethylhexyl)thiophen-2-yl)benzo[1, 2- b :4, 5- b ′]dithiophene (BDT-T) and fluorinated BDT-T (BDT-T-2F) units are designed and synthesized based on a random polymerization strategy. The terpolymers demonstrate wide optical bandgaps larger than 2.0 eV. Compared to the host polymer PB2, the terpolymers exhibit downshifted energy levels and enhanced crystallinities, which show much lower energetic disorders. After blending with a wide bandgap non-fullerene acceptor FTCC-Br, the optimized terpolymer shows a much faster charge transfer rate than PB2 . Importantly, the OPV cell based on PB3:FTCC-Br achieves a high power conversion efficiency of over 15% with an open-circuit voltage ( V OC ) of 1.06 V under one sun illumination. The PB4:FTCC-Br-based cell demonstrates a PCE of 14.79% with a high V OC of 1.09 V. It also should be noted that the PB3:BTP-eC9-based cell exhibits a PCE of 18.28%. Besides, the PB4:FTCC-Br-based cell with an effective area of 1.0 cm 2 exhibits a PCE of over 31% under 2700 K illumination of 1000 lux. The results indicate that the ternary copolymerization strategy is an effective way to fine-tune the opto-electronic properties of highly efficient polymer donors for versatile photovoltaic applications.